2019
DOI: 10.1007/s00003-019-01229-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the contamination levels of dried teas and their infusions by polycyclic aromatic hydrocarbons (PAHs)

Abstract: The occurrence of 16 polycyclic aromatic hydrocarbons (PAHs) in 68 brands of teas, bought in Poland, was surveyed using ultrasonic extraction of dried teas and liquid-liquid extraction of infusions. The extracts were cleaned by solid phase extraction. The instrumental analysis was performed using gas chromatography coupled with mass spectrometry (GC-MS). The total content of 16 PAHs ( P 16PAHs) ranged from 41.5 to 2910.2 lg/kg in dried teas and from 52.9 to 2226.0 ng/L in infusions. Benzo(a)pyrene was found fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…In turn, Ishizaki et al [ 42 ] examined PAH contents in tea and herb samples and showed that the mint herb contained a high content of phenanthrene (23.1 ng/g), pyrene (19.4 ng/g) and fluoranthene (22.5 ng/g). The presence of PAHs in mint tea samples from the Polish market was confirmed by Ciemniak et al [ 43 ], with high content of phenanthrene (49.9 µg/kg) and fluoranthene (39.0 µg/kg).…”
Section: Resultsmentioning
confidence: 70%
“…In turn, Ishizaki et al [ 42 ] examined PAH contents in tea and herb samples and showed that the mint herb contained a high content of phenanthrene (23.1 ng/g), pyrene (19.4 ng/g) and fluoranthene (22.5 ng/g). The presence of PAHs in mint tea samples from the Polish market was confirmed by Ciemniak et al [ 43 ], with high content of phenanthrene (49.9 µg/kg) and fluoranthene (39.0 µg/kg).…”
Section: Resultsmentioning
confidence: 70%
“…In Poland, 68 brands of dried tea and infusions were evaluated by Ciemniak et al [121]. They observed 16 PAHs concentrations varying between 41.5-2910.2 and 52.9-2226.0 µg/kg in dried teas and infusions, respectively.…”
Section: Other Productsmentioning
confidence: 99%
“…PAHs are known to be formed by condensation processes of smaller organic compounds in absence of oxygen by either pyrolysis or pyrosynthesis (Ciemniak et al 2019). Pyrolysis (pyro meaning "fire" and lysis for "separating") is the decomposition of organic material at elevated temperatures in an inert atmosphere and it involves irreversible change of chemical composition and physical phase (Viegas et al 2019).…”
Section: The Formation Mechanism Of Pahsmentioning
confidence: 99%